Water-assisted ketonization of methyl palmitate to palmitone over metal incorporated TiO2 catalysts - Jetsadagorn Pittayatornkul; Tosapol Maluangnont; Siriporn Jongpatiwut; Piyasan Praserthdam; Makoto Ogawa; Tawan Sooknoi (Reaction Chemistry & Engineering, 2024)
Over 0.5Pd/TiO 2 , water promotes hydrolysis of methyl palmitate to palmitic acid that undergoes ketonization to palmitone. Pd dissociates H 2 and facilitates H 2 -spillover for the generation and recovery of Lewis Ti 3+ active sites.
Keywords: Zeolite Catalysis and Synthesis; Catalysis for Biomass Conversion; Membrane Separation and Gas Transport